Climate change and the sustainability of agricultural productivity in Brazil - Pires, Gabrielle Ferreira (Universidade Federal de Viçosa, 2015)
There is a wide global expectation that Brazilian total agricultural output will increase like no other country in the world to meet the projected higher demand for food until 2050. While trying to meet this expectation, Brazil will face the effects of a severe climate change induced by the change in atmospheric composition. In addition, if the future increase in total production resembles the dynamics of the past and increasingly deforest natural biomes as the Amazon and the Cerrado, we run a great risk, as recent studies indicate that large-scale deforestation drives significant changes in water availability and could have implication for agricultural systems. This thesis investigates how climate change and additional deforestation may affect the productivity of the main commodities exported by the country until 2050: soybeans and cattle pasture. We used a gridded crop model to assess the effects of the climate simulated by four CMIP5 models under the IPCC AR5 RCP8.5 scenario on soybean and pasture productivity. We contrasted these results with a second group of simulations that account for the effects of more severe Amazon and Cerrado deforestation scenarios on regional climate. Soybean simulations show that, for central-northern Brazilian productive regions, the effects of climate change are dependent on the planting dates. The productivity of soybean cultivars planted in late September, sowed early by farmers who choose to adopt double-cropping systems (two crops on the same land in the same agricultural calendar) is predicted to expressively decrease. However, soybean cultivars that are planted in later dates (November- December), mainly sowed by farmers who choose to grow only one crop in the agricultural calendar, show increased productivity. The decrease in productivity for earlier dates is related to a sharper decreasing trend in precipitation during these months of the year, while the increased productivity in later dates is due to a smaller water deficit and the positive effects of an increased atmospheric CO 2 concentration. Southern Brazilian productive regions also show increased soybean productivity until the middle of the century, despite the planting date. For central-northern Brazilian productive regions, moving planting dates from September to later dates expressively increases soybean productivity, but decreases the probability of adopting double-cropping systems. In addition, increased levels of deforestation lead to increased soybean productivity loss. Pasture simulations show that, as well as in the case of soybeans, pasture productivity is predicted to decrease in central-northern Brazilian regions and slightly increase in southern regions. In addition, higher deforestation levels causes further productivity decrease, and lead to at least twice as large productivity losses. According to all simulations in this work, the regions most affected are either the major Brazilian production region (Mato Grosso) or where the exploration has begun more recently and still hold an expressive agriculture potential as MATOPIBA, indicating that government investments in these regions without the proper consideration of the climate risks are a high-risk strategy. Finally, in the face of climate change and with little evidence that deforestation in Amazonia and Cerrado is ending, Brazil needs to review its agriculture and conservation policies and immediately shift to a new standard of zero deforestation in Amazonia and Cerrado, and create mechanisms to identify and trace solutions to adapt its agriculture to climate change.

Há uma grande expectativa global de que produção agrícola total do Brasil irá aumentar como em nenhum outro país do mundo para atender ao aumento da demanda por alimentos até 2050. Ao tentar atender a essa expectativa, o Brasil terá de enfrentar os efeitos de uma grave mudança climática induzida pela mudança na composição atmosférica. Além disso, se o futuro aumento da produção total se assemelhar a dinâmica do passado e a fronteira agrícola avançar sobre biomas naturais como a Amazônia e o Cerrado, corremos um grande risco. Estudos recentes indicam que o desmatamento em grande escala causa mudanças significativas na disponibilidade de água no ambiente e poderia ter implicações para os sistemas agrícolas. Esta tese investiga como a mudança climática e o desmatamento adicional podem afetar a produtividade das principais commodities exportadas pelo país até 2050: soja e pastagens para criação de gado. Foi utilizado um modelo de culturas agrícolas para avaliar os efeitos do clima simulado por quatro modelos do CMIP5 sob o cenário RCP8.5 do IPCC AR5 na produtividade de soja e pastagens. Estes resultados foram contrastados com um segundo grupo de simulações que representam os efeitos de cenários de desmatamento mais severos da Amazônia e do Cerrado no clima regional. As simulações de soja indicam que, dentre as regiões mais produtivas no centro-norte do Brasil, os efeitos das alterações climáticas são dependentes das datas de plantio. A produtividade das cultivares de soja plantadas em setembro, semeadas mais cedo por agricultores que optam por adotar sistemas safra-safrinha (duas culturas no mesmo espaço no mesmo calendário agrícola) deve diminuir expressivamente. No entanto, cultivares de soja que são plantadas em datas posteriores (novembro- dezembro), semeadas principalmente por agricultores que optam por cultivar apenas uma cultura no mesmo calendário agrícola, mostram um aumento da produtividade. A diminuição da produtividade para datas precoces está relacionada a uma tendência de diminuição mais acentuada da precipitação durante estes meses do ano, enquanto o aumento da produtividade em datas mais tardias é devido a um déficit hídrico menor e os efeitos positivos de um aumento da concentração de CO 2 atmosférico. Regiões produtoras do Sul do Brasil também mostram aumento da produtividade de soja até o meio do século, independentemente da data de plantio. Para as regiões produtivas do centro e norte do Brasil, movendo-se as datas de plantio de setembro para datas posteriores pode levar a um aumento da produtividade de soja, mas diminui a probabilidade de adoção de sistemas safra-safrinha. Além disso, cenários de desmatamento mais severos levam a um aumento da perda de produtividade de soja. As simulações de produtividade de pastagens mostram que, assim como no caso da soja, a produtividade das pastagens deve diminuir em regiões centrais e do norte do Brasil e aumentar ligeiramente nas regiões sul. Além disso, níveis mais elevados de desmatamento provocam maior redução da produtividade, e conduzem a perdas de produtividade pelo menos duas vezes maiores. De acordo com todas as simulações deste trabalho, as regiões mais afetadas são onde estão localizados os maiores produtores agrícolas nacionais (Mato Grosso) ou em regiões que começaram a ser exploradas mais recentemente e ainda guardam elevado potencial agrícola como o MATOPIBA, indicando que investimentos do governo nessas regiões sem a consideração apropriada dos riscos climáticos é uma estratégia de elevado risco. Finalmente, em face às mudanças climáticas e com reduzida evidência de que o desmatamento na Amazônia e no Cerrado estejam chegando a um fim, o Brasil deverá rever suas políticas agrícolas e conservacionistas e alcançar imediatamente níveis de desmatamento zero nestes biomas, e criar mecanismos para identificar e traçar soluções para adaptar sua agricultura às mudanças climáticas.
Mudanças climáticas e a sustentabilidade da produtividade agrícola no Brasil
Keywords: Meteorologia agrícola; Climatologia agrícola; Desmatamento; Mudanças climáticas; Produtividade agrícola; Sustentabilidade; Agronomia